"We out here and we've been here": the role of university archives in student-led campus history initiatives to remember and reassert black presence in American higher education. Issue 1 (January 2020) - Gosselar, Ashley
Abstract : Student activists at American universities are scrutinizing the archival record to uncover documentation of African Americans on campus and working to amend the built environment by changing building names, removing statues that memorialize a racist past and creating counterspaces that reassert the presence of African Americans in campus history. Examples include the "Black at Bryn Mawr" walking tour and the "Monumental Women Project" at the University of Chicago. These initiatives foster what Michelle Caswell, Marika Cifor and Mario Ramirez have termed "representational belonging" for students of color at predominately white institutions. This article highlights examples of this student-led work, explores the role of University Archives in representational belonging and points to archivists who are advancing social justice by collecting and promoting records of students of color.